Fidelity in the use of app for solving differential equations - Alberto Camacho Ríos; Marisela Ivette Caldera Franco; Verónica Valenzuela González (Universidad de Guadalajara, 2019)
This report shows the results of using Computational Algebraic Applications (CAA) for mobile devices, intended as aid in college courses of Ordinary Differential Equations (ODE). The main purpose was for students to gain skills in such software so they could proficiently solve ODEs as well as to provide graphics from the solutions obtained. From the "fidelity" concept of the software, several applications were analyzed and evaluated such as: Differential Equations, Wolfram, Desmos, Photomath, among others. The given results proved than those applications were the most useful. With those results, a Didactic Situation was created in which students interacted with the app to solve equations and to graph results. The results shows some deficiencies in the interface evolution of the app that was used, this cause significant didactic phenomena.